2019
DOI: 10.1002/hep.30597
|View full text |Cite
|
Sign up to set email alerts
|

Dual Specificity Phosphatase 12 Regulates Hepatic Lipid Metabolism Through Inhibition of the Lipogenesis and Apoptosis Signal–Regulating Kinase 1 Pathways

Abstract: Nonalcoholic fatty liver disease (NAFLD) has become the most common cause of chronic liver disease worldwide. Due to the growing economic burden of NAFLD on public health, it has become an emergent target for clinical intervention. DUSP12 is a member of the dual specificity phosphatase (DUSP) family, which plays important roles in brown adipocyte differentiation, microbial infection, and cardiac hypertrophy. However, the role of DUSP12 in NAFLD has yet to be clarified. Here, we reveal that DUSP12 protects agai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
47
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 44 publications
3
47
0
Order By: Relevance
“…As a MAPKKK, ASK1 acts as a master switch of cell death: it initiates and sustains activation of two MAPKs (p38 and JNK) to induce apoptosis. Since ASK1 is over‐activated in liver tissues during NAFLD, ASK1 critically involved in liver inflammation and thought to be an ideal druggable target of NAFLD . Based on our findings, inhibition on the activation of ASK1 pathway and its downstream JNK and p38 signals by melatonin could be a promising strategy to alleviate NAFLD.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…As a MAPKKK, ASK1 acts as a master switch of cell death: it initiates and sustains activation of two MAPKs (p38 and JNK) to induce apoptosis. Since ASK1 is over‐activated in liver tissues during NAFLD, ASK1 critically involved in liver inflammation and thought to be an ideal druggable target of NAFLD . Based on our findings, inhibition on the activation of ASK1 pathway and its downstream JNK and p38 signals by melatonin could be a promising strategy to alleviate NAFLD.…”
Section: Discussionmentioning
confidence: 69%
“…Thus, ASK1 is involved in the development of various diseases, including tumorigenesis, neutrophilic dermatosis, cardiac hypertrophy, diabetes, and acquired immunodeficiency syndrome . For the past few years, several investigations have showed that ASK1 is continuously over‐activated in liver during NAFLD progression, and inactivation of ASK1 might remedy NAFLD . A very recent clinical study showed that a selective ASK1 inhibitor reduced liver fibrosis in patients with NASH …”
Section: Introductionmentioning
confidence: 99%
“…In this issue of Hepatology , Huang and colleagues report a very interesting study addressing the regulatory mechanisms underlying ASK1 activation. Using gain‐of‐function and loss‐of‐function studies in vitro and in vivo , they show that DUSP12, a member of the dual‐specific phosphatase (DUSP) family, regulates hepatic lipotoxicity through inhibition of the ASK1 signal cascade (Fig.…”
mentioning
confidence: 99%
“…Using gain‐of‐function and loss‐of‐function studies in vitro and in vivo , they show that DUSP12, a member of the dual‐specific phosphatase (DUSP) family, regulates hepatic lipotoxicity through inhibition of the ASK1 signal cascade (Fig. ) …”
mentioning
confidence: 99%
See 1 more Smart Citation